Epidemiology of invasive fungal disease in haematologic patients. Issue 3 (16th November 2020) - Souza, Luciana; Nouér, Simone A.; Morales, Hugo; Simões, Belinda; Solza, Cristiana; Queiroz‐Telles, Flavio; Nucci, Marcio
Abstract: Invasive fungal disease (IFD) is frequent in patients with haematologic malignancies and in recipients of haematopoietic cell transplantation (HCT). An epidemiologic study conducted in Brazil reported a high incidence of IFD in haematologic patients, and invasive fusariosis was the leading IFD. A limitation of that study was that galactomannan was not available for at least half of the study period. In order to characterise the epidemiology and burden of IFD in three cohorts, HCT, acute myeloid leukaemia (AML) or myelodysplasia (MDS), and acute lymphoid leukaemia (ALL), we conducted a prospective multicentre cohort study in four haematologic Brazilian centres. From August 2015 to July 2016, all patients receiving induction chemotherapy for newly diagnosed or relapsed AML, MDS or ALL, and all HCT recipients receiving conditioning regimen were followed during the period of neutropenia following chemotherapy or the conditioning regimen. During a 1‐year period, 192 patients were enrolled: 122 HCT recipients (71 allogeneic, 51 autologous), 46 with AML, and 24 with ALL. The global incidence of IFD was 13.0% (25 cases, 11 proven and 14 probable). Invasive aspergillosis (14 cases) was the leading IFD, followed by candidemia (6 cases) and fusariosis (3 cases). The incidence of IFD was 26.1% in AML/MDS, 16.7% in ALL, 11.3% in allogeneic HCT, and 2.0% in autologous HCT. The burden of IFD in haematologic patients in Brazil is high, with a higher frequency in AML and ALL. Invasive aspergillosis is the leading IFD, followed by invasive candidiasis and fusariosis.